The Influence of Organizational Culture and Motivation on Performance with Competence as an Intervening Variable in the Financial Management Agency Regional Income and Assets of Binjai City - Dt. Majo Basa, Yuanda; Isa Indrawan, Muhammad (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
This study aims to analyze the influence of organizational culture and motivation on performance with competence as an intervening variable. The type of research used is associative quantitative. This research was conducted at the Office of Regional Income and Assets Financial Management Agency, Binjai City. The population of this research is 173 employees. The sample technique used is a saturated sample. The data source is primary. The research model used is Path Analysis and the measurement tool used is Smart PLS version 3.3.3. The results of his research are as follows Organizational Culture has a positive and significant effect on performance. Organizational Culture has a positive and significant effect on competence. Competence has no significant positive effect on performance. Motivation has no significant positive effect on performance. Motivation has a positive and significant effect on competence. Organizational Culture has no significant positive effect on Performance through Competence. Motivation has a positive and insignificant effect on performance through competence.